2021
DOI: 10.3390/app11167400
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design Evaluation Considering Confidence Based on Z-AHP-TOPSIS Method

Abstract: In concept design, effective decision making and management of schemes can shorten the design cycle and improve product quality. The decision maker (DM)’s confidence is one of the critical factors affecting the conceptual design evaluation. Although many studies use quantitative linguistic evaluation for design scheme decision-making, which improves product conceptual design decision-making efficiency and effectiveness, few studies consider the confidence level of a decision. A conceptual design evaluation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Although the methods of concept design evaluation have been continuously optimized, the evaluation criteria used in these studies are still mainly based on traditional survey methods such as expert opinion 34 , 36 , 44 , literature review 4 , 34 , 37 , 41 and questionnaires 18 , 35 , which are feasible but have obvious drawbacks such as time-consuming, slow feedback, low user involvement, and small research These methods are feasible but have obvious drawbacks, such as time-consuming, slow feedback, low user participation, and small scope. A prerequisite for effective methods to obtain accurate and objective product concept evaluation results is the establishment of comprehensive and objective evaluation criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the methods of concept design evaluation have been continuously optimized, the evaluation criteria used in these studies are still mainly based on traditional survey methods such as expert opinion 34 , 36 , 44 , literature review 4 , 34 , 37 , 41 and questionnaires 18 , 35 , which are feasible but have obvious drawbacks such as time-consuming, slow feedback, low user involvement, and small research These methods are feasible but have obvious drawbacks, such as time-consuming, slow feedback, low user participation, and small scope. A prerequisite for effective methods to obtain accurate and objective product concept evaluation results is the establishment of comprehensive and objective evaluation criteria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3 and their weight values (Table 6 ) to apply the PFTOPSIS model to the conceptual design of kitchen waste containers discussed by Liu et al 18 . Ten participants were appointed randomly to form a decision panel to express their viewpoints on the conceptual design options in linguistic terms (Table 7 ) after learning about the four conceptual design options for kitchen waste containers shown by Liu et al 18 . Table 10 presents the collated decision matrix, Table 11 shows the corresponding Pythagorean fuzzy PIS and NIS, and Table 12 provides the distances of the conceptual design solutions from the Pythagorean fuzzy PIS and NIS, along with the revised closeness of the conceptual design solutions and the final ranking of the solutions.…”
Section: An Empirical Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Some scholars have also applied different quantitative methods to product innovation design or product evaluation in the last two years. Oey et al [23] sought a way to accommodate user requirements in their product and process improvement, Lu et al [24] constructed a product form evolution design method integrating the TRIZ contradiction matrix to simplify the product form evolution process, Liu et al [25] proposed a conceptual design evaluation method based on Z-numbers, Yue et al [26] improved the evaluation system of the design of household medical products for the elderly, Zhang et al [27] proposed a lead user identification method based on user behavior data and contribution content analysis, Wang et al [28] proposed a product evaluation method that combines natural language processing techniques and fuzzy multicriteria decision-making, and Wurster et al [29] used consumers as a valuable source of information to specify features of the output of an innovative CE ecosystem. e overall comparison between this article and previous studies is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%